A Raman Spectroscopic Study of Calcium Silicate Hydrate (CSH) in the Cement Matrix with CNTs and Oxide Additives - Azeem, Muhammad; Saleem, Muhammad Azhar (Journal of Spectroscopy, 2022)
The calcium silicate hydrate (CSH) concentration in the cement paste mixed with different types of carbon nanotubes (CNTs) and oxide additives is compared by using Raman spectroscopy. The pristine, hydroxyl and carboxyl functionalized CNTs are used in this work. The oxide additives are zinc oxide (ZnO), gadolinium oxide (Gd2O3), and silicon oxide (SiO2). A laser wavelength of 785 nm was used to collect the Raman spectra. It was observed that the concentration of calcium silicate hydrate (CSH) is unaffected in CNTs-OPC matrices regardless of the type and weight percentage of the CNTs. The oxides, as expected, show significant effects on the concentration of the CSH in the matrices. An increase in the CSH concentration is observed in the ZnO and Gd2O3 matrices with cement. For the SiO2 cement paste matrix, however, the CSH concentration appears to be decreased. This study shows CSH concentration can be controlled by using oxide additives whereas CNTs do not react chemically with the cement composites.